1997
DOI: 10.1590/s0103-06631997000300002
|View full text |Cite
|
Sign up to set email alerts
|

Observations on Etched Enamel in Non-Erupted Deciduous Molars: A Scanning Electron Microscopic Study

Abstract: Under the scanning electron microscope, the characteristics of the buccal surface enamel of human non-erupted deciduous molars were evaluated after using 15, 30, and 45 seconds of phosphoric acid etching time. The teeth were extracted, kept in a 70% alcohol solution and later dehydrated and metallized for analysis with the scanning electron microscope JEOL, JSM-6.100. The in vitro experiment with 35% phosphoric acid revealed that there is a tendency of predominance of interprismatic enamel dissolution or type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
2
0
2
Order By: Relevance
“…In fact, Costa et al 4 (1998) reported a random distribution of demineralization patterns in unerupted deciduous teeth etched with 35% phosphoric acid. However, Fava et al 7 (1997), using the same technique, though with a larger number of samples, found a slightly greater prevalence of type II demineralization, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, Costa et al 4 (1998) reported a random distribution of demineralization patterns in unerupted deciduous teeth etched with 35% phosphoric acid. However, Fava et al 7 (1997), using the same technique, though with a larger number of samples, found a slightly greater prevalence of type II demineralization, which is in agreement with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In other situations, the maximum demineralization is in peripheral interprismatic areas with the center of the prism integral [35]. Also, in cases where both types of demineralization coexist, an irregular amorphous relief is obtained after conditioning with 37% orthophosphoric acid for 15 seconds [35,36].…”
Section: Afm Analysismentioning
confidence: 99%
“…For young people, where the interprismatic organic substance is more resistant to acid attack, it is well represented, like enamel rich in acid-resistant fluorapatite crystals, the relief obtained after conditioning acid will be less retentive and irregular. [35][36][37].…”
Section: Afm Analysismentioning
confidence: 99%
“…Quinze espécimes foram testados para cada solução ácida. O autor utilizou um grupo controle onde a superfície do esmalte não foi condicionada com soluções ácidas, apenas polida com , em 1980, avaliaram a resistência adesiva de sistemas adesivos ao esmalte empregando diferentes concentrações de ácido fosfórico(10,20,30,40,50, 60 e 70% w/w%). Setenta incisivos centrais humanos foram utilizados para o estudo.…”
unclassified